2017
DOI: 10.1002/ange.201701867
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Phosphane‐Substituted Disilene

Abstract: There is growing interest in compounds containing functionalizedE = Em ultiple bonds (E = Si, Ge,S n, Pb) because of their potential to exhibit novel physical and chemical properties.However,compounds containing multiple functionalizations are rare,w ith scarcity increasing with increasing degree of substitution. The first ditetrelene R 2 E=ER 2 in which the E=Eb ond is substituted by four heteroatoms (other than Si)i sd escribed. The tetraphosphadisilene {(Mes) 2 P} 2 Si = Si{P(Mes) 2 } 2 (7)i sr eadily isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The bond between the carbene carbon and the phosphorus atom (C1–P1/C21–P2) is 1.7501(10)/1.7501(10) Å, which is slightly longer than those reported in the literature for cAACP–PcAAC and cAACN–PcAAC (1.719 Å in both these cases), thus indicating the presence of less double-bond character between the phosphorus and the carbene carbon atoms in compound 2 . The Si–P bond distances [Si1–P1 2.2238(4), Si1–P2 2.2228(4)] are shorter than the Si–P single bond length {2.2448(7) and 2.2483(7)} in {(Dipp) 2 P} 2 SiCl 2 and 2.2572(8) Å in LSi­(Cl 2 )–P­(cAAC) [L= benzamidinate; PhC­(N t Bu) 2 ].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The bond between the carbene carbon and the phosphorus atom (C1–P1/C21–P2) is 1.7501(10)/1.7501(10) Å, which is slightly longer than those reported in the literature for cAACP–PcAAC and cAACN–PcAAC (1.719 Å in both these cases), thus indicating the presence of less double-bond character between the phosphorus and the carbene carbon atoms in compound 2 . The Si–P bond distances [Si1–P1 2.2238(4), Si1–P2 2.2228(4)] are shorter than the Si–P single bond length {2.2448(7) and 2.2483(7)} in {(Dipp) 2 P} 2 SiCl 2 and 2.2572(8) Å in LSi­(Cl 2 )–P­(cAAC) [L= benzamidinate; PhC­(N t Bu) 2 ].…”
mentioning
confidence: 77%
“…It is worth mentioning that the stabilization of phosphorus­(III) coordinated silylene failed from the reduction of {(Mes) 2 P} 2 SiCl 2 with 2 equiv of KC 8 , which gave complex {(Mes) 2 P} 3 SiK-(THF) 3 }. The latter was supported by only NMR spectroscopy …”
mentioning
confidence: 99%
“…In spite of the foregoing, we have recently shown that a careful choice of substituent at phosphorus enables the isolation of a fully‐phosphanyl‐substituted disilene {(Mes) 2 P} 2 Si=Si{P(Mes) 2 } 2 ( 2 ), [13] the first example of a fully heteroatom‐substituted ditetrelene in which the heteroatoms possess a lone pair (Mes=2,4,6‐Me 3 C 6 H 2 ). Unfortunately, 2 proved insoluble, even in strong donor solvents such as THF, preventing a detailed study of its reactivity.…”
Section: Introductionmentioning
confidence: 99%